2013
DOI: 10.3892/or.2013.2348
|View full text |Cite
|
Sign up to set email alerts
|

Genetic inhibition of vascular endothelial growth factor receptor-1 significantly inhibits the migration and proliferation of leukemia cells and increases their sensitivity to chemotherapy

Abstract: Little is known about the role of vascular endothelial growth factor (VEGF) receptor-1 (VEGFR-1) in acute leukemia. In this study, using real-time PCR and ELISA, we found that VEGF and VEGFR-1 are highly expressed in U937 leukemia cells and primary leukemia cells (M4/M5 subtypes), which are associated with an increased migration rate and extramedullary disease. In order to elucidate the role of VEGFR-1 in acute leukemia, we used a lentivirus-mediated shRNA expression system to specifically inhibit VEGFR-1 expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…In an attempt to uncover the cellular mechanism of fucoidan-mediated inhibition of ERK1/2, all the known mutations and receptor expression of the different types of cancer cells were assessed [95,129,130,131]. However, there was no clear mutation or absence of a particular receptor which was connected with the failure to inhibit the ERK1/2 expression.…”
Section: Summary Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In an attempt to uncover the cellular mechanism of fucoidan-mediated inhibition of ERK1/2, all the known mutations and receptor expression of the different types of cancer cells were assessed [95,129,130,131]. However, there was no clear mutation or absence of a particular receptor which was connected with the failure to inhibit the ERK1/2 expression.…”
Section: Summary Of Literaturementioning
confidence: 99%
“…For some cancer cell lines, we found clues in the existing literature that might serve as an explanation. For instance, U937 leukemia cells have constitutive low MAPK activity and have proven to be more resistant for MAPK-targeting therapies [129]. It was not possible to extrapolate it to the other unaffected cancer cells.…”
Section: Summary Of Literaturementioning
confidence: 99%
“…FLT-1 is commonly expressed in childhood ALL, 6,7 and VEGFA/FLT-1 signaling promotes migration and survival of leukemic cells in vivo and vitro. 6,8 Bevacizumab is a VEGFA-neutralizing antibody used in the treatment of several non-hematological cancers, and we tested its impact on mice with CNS involvement in our xenograft model. Recipients with equivalent levels of BM engraftment (Figure 2A), and therefore presumably similar levels of CNS involvement, were given intraperitoneal injections of either bevacizumab or saline.…”
mentioning
confidence: 99%
“…Previous studies have shown that increased levels of Helios Treg cells promoted angiogenesis in the bone marrow of ALL mice via the VEGFA/VEGF receptor 2 pathway [27]. Furthermore, FLT-1 is generally expressed in pediatric ALL and VEGFA/FLT-1 signaling enhances the migration and survival of leukemia [28,29]. FLT-1 activation on ALL cells results in cell migration and proliferation in vitro.…”
Section: Discussionmentioning
confidence: 99%